A Nanoplasmonic-Based Biosensing Approach for Wide-Range and Highly Sensitive Detection of Chemicals - Francesco Arcadio; Luigi Zeni; Aldo Minardo; Caterina Eramo; Stefania Di Ronza; Chiara Perri; Girolamo D’Agostino; Guido Chiaretti; Giovanni Porto; Nunzio Cennamo (Nanomaterials, 2021)
In a specific biosensing application, a nanoplasmonic sensor chip has been tested by an experimental setup based on an aluminum holder and two plastic optical fibers used to illuminate and collect the transmitted light. The studied plasmonic probe is based on gold nanograting, realized on the top of a Poly(methyl methacrylate) (PMMA) chip. The PMMA substrate could be considered as a transparent substrate and, in such a way, it has been already used in previous work. Alternatively, here it is regarded as a slab waveguide. In particular, we have deposited upon the slab surface, covered with a nanograting, a synthetic receptor specific for bovine serum albumin (BSA), to test the proposed biosensing approach. Exploiting this different experimental configuration, we have determined how the orientation of the nanostripes forming the grating pattern, with respect to the direction of the input light (longitudinal or orthogonal), influences the biosensing performances. For example, the best limit of detection (LOD) in the BSA detection that has been obtained is equal to 23 pM. Specifically, the longitudinal configuration is characterized by two observable plasmonic phenomena, each sensitive to a different BSA concentration range, ranging from pM to µM. This aspect plays a key role in several biochemical sensing applications, where a wide working range is required.